Kartosuwiryo dan NII: Kajian Ulang - Azra, Azyumardi (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2014)
Formichi, Kiara, Islam in The Making of The Nation: Kartosuwiryo and Political Islam in 20th Century Indonesia. Verhandelingen van het Koninklijk Instituut voor Taal-, Land- en Volkenkunde, 282, Leiden: KITLV Press, 2012, xvii, 244 pp. (map), USD 49.00, paper, ISBN 978-90-6718-386-4Chiara Formichi’s book, Islam and the Making of the Nation: Kartosuwiryo and Political Islam in 20th Century Indonesia (2012), is the most recent work on Kartosuwiryo and Negara Islam Indonesia (NII). Formichi perceives Kartosuwiryo and NII as Islamic political movement while discussing the place of Islam and Indonesian Muslims in the nation-state building. She argues that Kartosuwiryo movement and NII is the true expression of political Islam which aims at establishing ‘a federal Islamic state of Indonesia’ by collapsing the Indonesian state with Pancasila as its philosophical foundation. In her opinion, the roots of NII’s political Islam could be traced to the works and political activism of Kartosuwiryo in Sarekat Islam (SI), the first Islamic national movement in Indonesia, established in 1911. However, Formichi does not explain why the ideas, movement, struggle as well as the trial of establishing an Islamic state in Indonesia failed as confirmed by the experience of Kartosuwiryo and NII.DOI: 10.15408/sdi.v21i1.883